2019
DOI: 10.1073/pnas.1820469116
|View full text |Cite
|
Sign up to set email alerts
|

Role of thyroid dysimmunity and thyroid hormones in endometriosis

Abstract: Endometriosis is characterized by the presence of ectopic endometrial cells outside the uterine cavity. Thyroid autoimmunity has been associated with endometriosis. This work investigated the potential pathophysiological link between endometriosis and thyroid disorders. Transcripts and proteins involved in thyroid metabolism are dysregulated in eutopic and ectopic endometrium of endometriotic patients, leading to resistance of ectopic endometrium to triiodothyronine (T3) action and local accumulation of thyrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
2
24
1
1
Order By: Relevance
“…We have found increased serum T3 levels with the progressions of endometriosis from stage 1 to stage 4. Similar to our finding, it has been reported that (Peyneau et al, 2019) that thyroid disorders are associated with severe forms of endometriosis. They found that proteins involved in thyroid metabolism were dysregulated in eutopic and ectopic endometrium of endometriotic patients, leading to resistance of ectopic endometrium T3 action (Peyneau et al, 2019).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We have found increased serum T3 levels with the progressions of endometriosis from stage 1 to stage 4. Similar to our finding, it has been reported that (Peyneau et al, 2019) that thyroid disorders are associated with severe forms of endometriosis. They found that proteins involved in thyroid metabolism were dysregulated in eutopic and ectopic endometrium of endometriotic patients, leading to resistance of ectopic endometrium T3 action (Peyneau et al, 2019).…”
Section: Resultssupporting
confidence: 93%
“…Similar to our finding, it has been reported that (Peyneau et al, 2019) that thyroid disorders are associated with severe forms of endometriosis. They found that proteins involved in thyroid metabolism were dysregulated in eutopic and ectopic endometrium of endometriotic patients, leading to resistance of ectopic endometrium T3 action (Peyneau et al, 2019). However, few others (Parasar et al, 2017) found that women suffering from endometriosis had higher rates of hypothyroidism.…”
Section: Resultssupporting
confidence: 93%
“…Tissue samples have been sutured with 4-0 nylon suture (Cummings and Metcalf, 1995), 7-0 polypropylene suture (Cohen et al, 2014), silk suture (Fainaru et al, 2008), braided silk suture (Efstathiou et al, 2005;Becker et al, 2008), or stuck to the wall with adhesive such as bonding agent 3M vetbond (Symons et al, 2020). Uterine tissue engrafted varied from one large (5 mm) piece (Peyneau et al, 2019) to up to six (2 mm) tissue punches (Kumar et al, 2014). Tissue was sutured or adhered to the peritoneum (Wilkosz et al, 2011;Mattos et al, 2019;Tal et al, 2019;Chang et al, 2020;Hattori et al, 2020;Li et al, 2020;Symons et al, 2020;Yoshino et al, 2020;Chen et al, 2021;Santorelli et al, 2021), intestinal mesentery (Mishra et al, 2020), abdominal wall (Peyneau et al, 2019), bowel mesentery (Ricci et al, 2011), and ovaries (Hayashi et al, 2020).…”
Section: Surgical Engraftmentmentioning
confidence: 99%
“…Oestrogen promotes the transplantation of endometrial tissue into the peritoneum, thereby affecting proliferation and immortalisation, and also causes local and systematic in ammation [8,11]. Of the in ammatory factors, it has been reported that autoimmunity plays a major role in the development of endometriosis, and the relationship between thyroid autoimmunity and endometriosis has been highlighted [12,13].…”
Section: Introductionmentioning
confidence: 99%